Interfaces in Social Innovation: an Action Research Story on a Tribal Women’s Collective - Sunil D. Santha; Asha Banu Soletti; Sowmya Balasubramanian (Glocalism: Journal of Culture, Politics and Innovation)
This paper examines the nature of social interfaces that has emerged in the context of social innovations with vulnerable and marginalised tribal communities along the Tansa Reservoir in Maharashtra, India. This paper is part of a larger action research project that strives towards improving the livelihoods of tribal women through collectives such as self-help groups. The analysis presented in this paper pertains to the experiences of 13 tribal women who have come forward to form a self-help group to supplement their livelihoods. According to the tribal women, the collective spaces that the self-help group provide has itself been termed as innovation. In the above-mentioned context, this paper specifically examines the nature of diverse values and beliefs, interests, knowledge and power among different actors involved in promoting livelihood-based women’s collectives. It also explores the nature of response among tribal women to the intervention of outside experts in the day-to-day activities of their collective. The findings of this paper illustrate the discontinuities associated with the collective and specifically on the nature of frictions, disagreements and conflicts between actors, which are mediated and transformed at critical junctures. This signifies an underlying asymmetry between the knowledge systems of tribal women and outside experts respectively. Furthermore, this paper argues that if not properly nurtured, such innovative collective spaces can become sites of domination and agents for the perpetuation of mere socio-technical interest. Instead, the discourse of social innovation needs to be socially embedded within the issues of rights, recognition, representation and empowerment of those people who are vulnerable and marginalised in the society.